EFFECT OF USING DIFFERENT RATIONS OF SODIUM BICARBONAT ON MILK COMPOSITION IN AWASSI EWES - Muthanna A. M. Tayeb (Mesopotamia Journal of Agriculture)
Twenty four Awassi ewes with an average body weight of (55 kg) (4) year old were divided into 3 groups each of 8 ewes and fed for 50 days on one of 3 rations to study effect of sodium bicarbonate on milk secretion and composition in lactating Awassi ewes. All groups were fed rations consisted mainly of barley. wheat bran and soybean meal. The first group (control) was fed without sodium bicarbonate. while groups (2 and 3) were fed with different levels of sodium bicarbonate (1.5 and 3) respectively. Levels of protein and energy were similar in the 3 rations. The results revealed no significant differences in average daily milk production. milk lactos and milk protein. There was a significant increase (P < 0.05) in milk fat content when use sodium bicarbonate (6.18, 6.30, 7.10 %) .milk lactos yield (21.74, 26.77, 30.11 %) . milk fat yield (23.49, 27.45, 34.56 %) and milk protein yield (15.80, 18.19, 20.41%) for the three treatments respectively. Moreover. the results showed that levels (1.5, 3) of sodium bicarbonate had a significant effect (P<0.05) on rumen liquor samples pH (5.18, 5.77, 6.34). ammonia nitrogen concentration (6.68 . 8.85 . 8.91 mmol 100mol of rumen liquor for three treatment respectively .Blood samples analysis showed that treatments had no significant effects on concentration of total protein, urea, glucose, triglyceride and cholesterol.